Visualization of security vulnerabilities through intrusion detection system - Ahmed, Ibrar; Faruqe, Farhana (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2007.